(untitled) (Práxis Educativa, 2022)
This paper aimed to carry out a detailed textual analysis of the Brazilian Inclusion Law (known in Brazil by the anacronym LBI), with a view to identifying perspectives and advances in relation to the rights of people with disabilities. The research, with a qualitative approach, used a descriptive design, whose analysis was carried out using the software Interface de R pour les Analyzes Multidimensionnelles by Textes et de Questionnaires (IRaMuTeQ®). It was identified that the LBI is of paramount importance for the construction of an independent life for people with disabilities and was structured in order to bring guarantees of rights, which, for years, were considered “favors” and/or assistance. It brings not only basic social rights, but also civil and political rights, removing these people from the condition of extreme dependence that, in many cases, were treated as incapable. Keywords: Brazilian Inclusion Law. People with disabilities.